Parental Challenges and the Performance of the Primary Pupils Under Modular Distance Learning Delivery: An Input to Proposed Parental Orientation Guide - Ma Christina O Bauyon; Lustina P Lapie; Consorcia S Tan; Lerma P Buenvenida; Marcial M Bandoy (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The study focused on determining the challenges of the parents in modular distance learning in new normal education and developing a parental orientation guide to help the parents in addressing the difficulties they are encountering in the new normal. The sequential explanatory mixed method research was utilized as an approach. There are 388 respondents who were chosen to answer through an online survey questionnaire and selected 10 participants were chosen through purposive sampling by which the participants share common experiences. The findings revealed a significant relationship between parental challenges in terms of instructional, personal, and parental involvement and the performance of the learners. The personal challenges predict singly and in combination with learning in a virtual setting the performance of the learners. There are suggested recommendations based on the results of the study, such as they may be equally prepared to educate their children at home even they are busy with their different schedules, may strengthen the collaborative work between the school and families through parent-teacher meetings, close monitoring, and facilitation that could encourage children to read. The themes that emerged from the testimonies of the participants were clustered into superordinate themes: (1) Why Can’t I Focus on Flexitime, (2) Parental Time Constraints, (3) Driven to Teach, (5) Compelled to Learn, (6) A Unique Child: Mood Setting, (7) The Power of Patience.